Legal Accountability and Policy Solutions for Illegal Oil Drilling Criminal Acts in Aceh - Ariq Tsuraya Rasmawan; Mulyadi Mulyadi (Law Development Journal, 2025)
Aceh's special status in managing oil and gas resources is regulated in Article 160 Paragraph 1 of Law Number 11 of 2006. The realization of Aceh's authority in managing oil and gas resources is achieved through the establishment of the Oil and Gas Management Agency, the Aceh Oil and Gas Management Agency (BPMA), a government institution formed to jointly manage and control upstream business activities in carrying out activities in the oil and gas sector. Although there is already an agency that oversees oil and gas management, its implementation is still ineffective, many people drill for oil illegally and cause fires that can claim lives. The purpose of this study is to determine the practice of illegal drilling in East Aceh Regency and its impact on the environment, society and efforts to manage sustainable natural resources. In this study, the research method used is the normative legal research method, namely legal research that uses empirical facts obtained through analysis of a problem. Data will be collected from various sources, including literature, legal documents (laws, regulations, policies, etc.) of case studies. In this study, the solution to the problem that can be provided is that BPMA together with PPSDM MIGAS Aceh can also overcome drilling problems that are caused by the financial conditions and difficulties of the Aceh people who still depend on oil and gas natural resources as a livelihood. By educating and providing job training for 6 months, people who are declared to have graduated from the job training program will receive worker certification and will receive wages legally and with permits, so that it is hoped that problems related to illegal drilling and problems of social conditions in the community can be resolved properly through this activity.